2021
DOI: 10.1097/iae.0000000000003330
|View full text |Cite
|
Sign up to set email alerts
|

The Rap Study, Report 5: Rediscovering Macular Neovascularization Type 3

Abstract: Retinal–choroidal anastomosis is an exclusive clinical finding of macular neovascularization Type 3 in eyes with neovascular age-related macular degeneration. Multifocal macular neovascularization Type 3 is usually bilateral, and the lesions develop simultaneously, but when the multifocal phenotype is unilateral, it appears before the development of the unifocal one in the contralateral eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Microvascular anomalies in eyes with neovascular and non-neovascular AMD include capillary dilations and telangiectasia that are associated with locally increased VEGF expression. 17,59-61 A recent study showed that 19/94 eyes with type 3 MNV exhibited an asymptomatic precursor stage on OCT. 44 Because lack of exudation and non-progression to type 3 MNV in our case might result from VEGF suppression, 62 longitudinal imaging is required to definitively place DRAMA in the progression sequence of type 3 MNV.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Microvascular anomalies in eyes with neovascular and non-neovascular AMD include capillary dilations and telangiectasia that are associated with locally increased VEGF expression. 17,59-61 A recent study showed that 19/94 eyes with type 3 MNV exhibited an asymptomatic precursor stage on OCT. 44 Because lack of exudation and non-progression to type 3 MNV in our case might result from VEGF suppression, 62 longitudinal imaging is required to definitively place DRAMA in the progression sequence of type 3 MNV.…”
Section: Discussionmentioning
confidence: 90%
“…In two anti-VEGF treated eyes of one patient with neovascular AMD, we compare longitudinal multimodal clinical imaging and histology of type 3 MNV and DRAMA ( Table 2, Table 4 ). Although one patient, the clinical and imaging characteristics are typical of multifocal type 3 MNV, including bilaterality (55% of cases) 44 and absence of type 1 MNV. 11-13, 44, 45 Type 3 MNV is distinguished by intraretinal origin, 1, 2, 46 frequent near-term bilateral involvement, 7-9 and significant choroidal thinning with reduced perfusion.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…If not punctually recognized and treated, Type 3 MNV can rapidly advance toward development of macular atrophy 11 and fibrotic scars. 12 Therefore, it is paramount to discover new multimodal imaging biomarkers to maximize the probability of detecting effectively treatable precursor lesions.…”
mentioning
confidence: 99%